2013
DOI: 10.1038/nn.3563
|View full text |Cite
|
Sign up to set email alerts
|

Differential triggering of spontaneous glutamate release by P/Q-, N- and R-type Ca2+ channels

Abstract: The role of voltage-gated Ca2+ channels (VGCCs) in spontaneous miniature neurotransmitter release is incompletely understood. Here we show that stochastic opening of P/Q-, N-, and R-type VGCCs accounts for ~50% of all spontaneous glutamate release at rat cultured hippocampal synapses, and that R-type channels play a far greater role in spontaneous than in action potential-evoked exocytosis. VGCC-dependent ‘minis’ show similar sensitivity to presynaptic Ca2+ chelation as evoked release, arguing for direct trigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
182
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(204 citation statements)
references
References 60 publications
20
182
2
Order By: Relevance
“…The probability of spontaneous fusion of a docked vesicle (in the readily releasable pool) is reported to be 0.002–0.006 per second per vesicle (about one in 200 each second) 77, 78, 79, 80. Release in the absence of an action potential can in principal either be intrinsically spontaneous or alternatively it can be triggered by a spontaneous rise in local Ca 2+ .…”
Section: Quantitative Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The probability of spontaneous fusion of a docked vesicle (in the readily releasable pool) is reported to be 0.002–0.006 per second per vesicle (about one in 200 each second) 77, 78, 79, 80. Release in the absence of an action potential can in principal either be intrinsically spontaneous or alternatively it can be triggered by a spontaneous rise in local Ca 2+ .…”
Section: Quantitative Considerationsmentioning
confidence: 99%
“…This happens at a rate of 0.012–0.033 s −1 at a typical central synaptic bouton 77, 78, 79, 80. Considering there are ~ 5 release ready (‘primed’) SV per bouton and, in our model, six SNAREpins per SV, the rate of spontaneous release of a single SNAREpin from its clamp is estimated to be 4 × 10 −4 –1.1 × 10 −3  s ‐1 .…”
Section: Figure A1mentioning
confidence: 99%
“…The BRP ring-like complex within the AZ surrounds a central core of VGCCs (Kittel et al, 2006). Interestingly, recent work in mammalian synapses has shown that stochastic opening of VGCCs in the AZ is responsible for a substantial proportion of spontaneous neurotransmitter release (Ermolyuk et al, 2013), and that AZ size positively correlates with the frequency of spontaneous neurotransmitter release (Holderith et al, 2012;Matz et al, 2010), presumably via altered VGCC occupancy. If enhanced spontaneous vesicle fusion in dysc and slo mutants was due to an increase in the number of VGCCs within the AZ, this effect should be suppressed by removing extracellular Ca 2+ .…”
Section: Dysc and Slo Inhibit Spontaneous Neurotransmitter Release VImentioning
confidence: 99%
“…More recently, the spontaneous opening of voltage-gated Ca 2+ channels, especially of R-type channels, was shown to contribute a significant fraction of spontaneous release in excitatory hippocampal synapses (ref. 63; but see ref. 64, which did not find a role for Ca 2+ channels at excitatory cortical synapses).…”
mentioning
confidence: 99%